Effectiveness of subnational implementation of minimum unit price for alcohol: policy appraisal modelling for local authorities in England. (21st December 2022) - Brennan, Alan; Angus, Colin; Pryce, Robert; Buykx, Penny; Henney, Madeleine; Gillespie, Duncan; Holmes, John; Meier, Petra S.
Abstract: Aims: Evidence exists on the potential impact of national level minimum unit price (MUP) policies for alcohol. This study investigated the potential effectiveness of implementing MUP at regional and local levels compared with national implementation. Design: Evidence synthesis and computer modelling using the Sheffield Alcohol Policy Model (Local Authority version 4.0; SAPMLA). Setting: Results are produced for 23 Upper Tier Local Authorities (UTLAs) in North West England, 12 UTLAs in North East England, 15 UTLAs in Yorkshire and Humber, the nine English Government Office regions and England as a whole. Cases: Health Survey for England (HSE) data 2011–13 ( n  = 24 685). Measurements: Alcohol consumption, consumer spending, retailers' revenues, hospitalizations, National Health Service costs, crimes and alcohol‐attributable deaths and health inequalities. Findings: Implementing a local £0.50 MUP for alcohol in northern English regions is estimated to result in larger percentage reductions in harms than the national average. The reductions for England, North West, North East and Yorkshire and Humber regions, respectively, in annual alcohol‐attributable deaths are 1024 (−10.4%), 205 (−11.4%), 121 (−17.4%) and 159 (−16.9%); for hospitalizations are 29 943 (−4.6%), 5956 (−5.5%), 3255 (−7.9%) and 4610 (−6.9%); and for crimes are 54 229 (−2.4%), 8528 (−2.5%), 4380 (−3.5%) and 8220 (−3.2%). Results vary among local authorities; for example, annual alcohol‐attributable deaths estimated to change by between −8.0 and −24.8% throughout the 50 UTLAs examined. Conclusions: A minimum unit price local policy for alcohol is likely to be more effective in those regions, such as the three northern regions of England, which have higher levels of alcohol consumption and higher rates of alcohol harm than for the national average. In such regions, the minimum unit price policy would achieve larger reductions in alcohol consumption, alcohol‐attributable mortality, hospitalization rates, NHS costs, crime rates and health inequalities.